How adenomyosis changes throughout pregnancy: A retrospective cohort study. Issue 3 (17th August 2022) - Bertucci, Emma; Sileo, Filomena G.; Diamanti, Marialaura; Alboni, Carlo; Facchinetti, Fabio; La Marca, Antonio
Abstract: Objective: To study how adenomyosis changes during pregnancy and to possibly correlate these changes to maternal and fetal outcomes. Methods: Retrospective exploratory cohort study including 254 women with a pre‐conceptional/first‐trimester scan to document adenomyosis and known obstetric outcome. If visible, adenomyosis signs were documented in each trimester and postpartum. Mann–Whitney U tests or χ 2 tests were used for continuous and categorical variables, respectively. Results: A globular uterus was reported in 79% ( n  = 52) of women with adenomyosis in the first trimester, in 38% ( n  = 20) and 2% ( n  = 1) of women in the second and third trimesters, respectively, and postpartum in 77% ( n  = 34) of women. Asymmetrical thickening ( n  = 20, 30%) and cysts ( n  = 15, 23%) were only visible in 1st trimester. Adenomyosis was associated with miscarriage (odds ratio [OR] 5.9, 95% confidence interval [CI] 2.4–14.9, P  < 0.001) also in normal conception only (OR 5.1, 95% CI 1.8–14.2, P  = 0.002) or adjusting for maternal age (adjusted OR 5.9, 95% CI 2.3–15.2, P  < 0.001). Gestational age at delivery was lower in adenomyosis ( P  = 0.004); the cesarean section rate was higher than in controls (OR 2.5, 95% CI 1.3–4.8, P  = 0.007) also adjusting for age (adjusted OR 2.07, 95% CI 1.06–4.08, P  = 0.035). Conclusions: Signs of adenomyosis were visible but progressively disappeared in pregnancy; adenomyosis was associated with an increased risk of early miscarriage. Prospective studies are needed to confirm our results. Synopsis: Sonographic signs of adenomyosis are visible in pregnancy although they progressively disappear; adenomyosis was associated with an increased risk of early miscarriage .